The political and economic challenges of energy in the Middle East and North Africa - Jalilvand, David Ramin (Global governance, 2018)
“The Middle East and North Africa (MENA) are in disarray, and shifts in the field of energy have the potential to drastically affect the course of political and economic developments in the region. Declining oil prices, skyrocketing domestic demand, the rise of unconventional oil and natural gas production in North America, as well as shifting patterns of global energy trade all put severe pressures on both producing and importing countries in the MENA region. Policy-makers are facing fundamental challenges in light of the duality of grand transformations in (geo)politics and energy. Changes in the field of energy require substantial political and economic reforms, affecting the very fabric of sociopolitical arrangements. At the same time, the MENA region's geopolitical volatility makes any such reforms extremely risky. Including contributions by academics and analysts from both inside and outside the MENA region, this volume explores the changes in global and regional energy, the impact of changing international energy dynamics on politics and economies in the MENA region, and the challenges that will result. This is essential reading for researchers, postgraduates, and professionals in Middle Eastern and North African politics, global energy governance and regionalism.” (Publisher's description)